Effects of misaligned wave and wind action on the response of the combined concept windwec - Karimirad, Madjid; Michailides, Constantine (My University, 2018)
In the present paper, the effects of misaligned wave and wind action on the dynamic response of the WindWEC combined concept are evaluated and presented. WindWEC is a recently proposed combined wind and wave energy system; a hybrid offshore energy system that consists of: (a) a 5MW floating wind turbine supported by a spar-type substructure (e.g. Hywind), a Wave Energy Converter (WEC) that is of heaving buoy type (e.g. Wavestar), (c) a structural arm that connects the spar with the WEC and (d) a common mooring system. Hybrid offshore platforms are combining wave and wind energy systems and are designed in order to gain the possible synergy effects and reduce the cost of generated electrical power while increasing the quality of delivered power to grids. During the lifetime of a combined concept, wave and wind can be misaligned which may affect the dynamic response and as a result the functionality of it. In particular, for asymmetric configurations, the misalignment of the wave and wind may result in unexpected behaviour and significant effects that may reduce the produced power. For the case of the WindWEC concept, the relative motion of the spar platform and WEC buoy results to the produced power. In this paper, the dynamic response and power production of the buoy type WEC and wind turbine are examined for different loading conditions where the wave and wind are misaligned. Integrated/coupled aero-hydro-servo-elastic time-domain dynamic simulations considering multi-body analyses are applied. The motion, structural and tension responses as well as power production are examined. The misalignment of wave and wind results to higher loads that affect the mooring line system and motion responses of the spar. It is found that the produced power of wind turbine is not significantly affected.
Keywords: Wind power; Wind turbines; Wave energy converters; Wind energy systems; Floating wind turbines; Electrical power